IDENTIFIKASI MISKONSEPSI MAHASISWA PROGRAM STUDI PENDIDIKAN FISIKA ANGKATAN 2018 UNIVERSITAS JEMBER PADA PEMAHAMAN KONSEP LISTRIK STATIS DAN DINAMIS - Fitriana Novitasari; Bambang Supriadi; Maryani Maryani (FKIP Universitas Jember, 2019)
Abstract This research was conducted based on the results of Based on the results of the analysis of the data obtained, it can be concluded that there are 15.3% of the answers in the conceptual understanding category, 5.1% of the answers in the conceptual understanding category but not sure, 35.6% of the misconception category answers and 44% of the answers in the category do not understand the concept. Students' understanding of the concept of static and dynamic electricity is still lacking. Key words: research, concept,